PEMBUATAN APLIKASI MONITORING (FILTERING) WEBSITE UNTUK PENGGUNAAN KOMPUTER DENGAN PEMROGRAMAN VISUAL - Armein Syahid; Dharma Liza Said; Yasdinul Huda (Universitas Negeri Padang, 2016)
The development of today's modern technological advances led to the need of the internet can not be avoided. The ability of the Internet as a modern media of information and communication can be an effective and efficient means for the exchange and dissemination of information globally unhindered by distance, time differences and geographical factors by users around the world. The use of the internet at the moment many abused for things that are negative as appearance of various kinds of websites that contain pornographic and more easily to get internet access extensively without strict control so it can be accessible to anyone, including minors. Monitoring and filtering action is required against these sites. This study aims to assist the government in the implementation of anti-pornography laws and the parents in monitoring their children by blocking sites that contain pornography. Blocking system in this website monitoring application (filtering) is based on code that has been made. This application is one kind of standalone application that can be run without the need for prior installation on Windows operating systems. For the manufacture of user interface used programming languages Visual Basic 2010.The results showed that the monitoring application can perform filtering by looking every caption on the programs that are running, and then match it with the program code that has been made. If there is a match, then the application will close the program. This application can be hidden so that computer users will not be aware of the time of filtering. This application also has a feature to store the results of monitoring during the computer is being used so that will be easier to control the use of computer. Keyword : Monitoring, Filtering, Pornography